2016
DOI: 10.3748/wjg.v22.i34.7708
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients after recovering from acute severe biliary pancreatitis

Abstract: Cholelithiasis is the most common cause of acute pancreatitis, accounting 35%-60% of cases. Around 15%-20% of patients suffer a severe attack with high morbidity and mortality rates. As far as treatment is concerned, the optimum method of late management of patients with severe acute biliary pancreatitis is still contentious and the main question is over the correct timing of every intervention. Patients after recovering from an acute episode of severe biliary pancreatitis can be offered alternative options in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 75 publications
1
10
0
4
Order By: Relevance
“…41.9% of severe cases had pancreatic necrosis whereas its reported incidence is 20-25% in the patients with severe pancreatitis [7] . Pseudocyst/walled off necrosis was observed in only 4.2% of the patients and was comparable to the studies [8] where it was 6-8%. Overall vascular complications are rare and, in our study, it was observed in 2%.…”
Section: Discussionsupporting
confidence: 86%
“…41.9% of severe cases had pancreatic necrosis whereas its reported incidence is 20-25% in the patients with severe pancreatitis [7] . Pseudocyst/walled off necrosis was observed in only 4.2% of the patients and was comparable to the studies [8] where it was 6-8%. Overall vascular complications are rare and, in our study, it was observed in 2%.…”
Section: Discussionsupporting
confidence: 86%
“…The therapeutic choices in later phase of SAP are based on the development and evolution of (peri) pancreatic fluid-necrotic gatherings and their septic complications [34]. The pathological basis of therapeutic program in the SAP are linked on the grade of impairment of pancreatic parenchyma and peripancreatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Another report by Dedemadi and his colleagues [65] published in 2016 noted that ERCP and ES in cases with AP who can not undergo cholecystectomy developed biliary events 0%-28.6%, recurrent pancreatitis 0%-8.2%, mortality 3%-4.7%. Other cases under conservative treatment had biliary events 9.4%-14.3%, recurrent pancreatitis 12%-23%, mortality 3.9%.…”
Section: Elective Ercp To Prevent Pancreatitis Recurrencementioning
confidence: 99%
“…Moreover, If we consider surgery for pancreatic cystic collections, pseudocysyt and or walled off necrosis, it should be performed at the same time with cholecystectomy [65].…”
mentioning
confidence: 99%